The effect of temperature and ploidy on skeletal anomaly prevalence in a fast growing phase in Atlantic salmon Salmo salar and molecular investigations on lower jaw deformity - Gianluca Amoroso; Mark Adams; Ventura, T; Christopher Carter; Battaglene, S; Elizur, A; Cobcroft, JM (2015)
Skeletal anomalies are found in farmed Atlantic salmon with triploids generally showing higher prevalence than diploids. The use of high temperature regimes in the hatchery phase of Atlantic salmon to accelerate growth has been reported as a critical factor affecting normal skeletal development. One skeletal anomaly, lower jaw deformity (LJD) is a downward curvature of the lower jaw that has a negative impact on production efficiency through product downgrading, and animal welfare via higher susceptibility to diseases and mortality. The causes of LJD are unknown, although it is more common in triploid fish. LJD may be triggered by environmental, nutritional or genetic factors in association with physiological characteristics of triploids. In order to assess the effect of ploidy and temperature on the prevalence of skeletal anomalies and to understand molecular mechanisms underlying the onset of LJD, diploid and triploid Atlantic salmon embryos were collected from a commercial hatchery and held and reared separately for nine months. After incubation at 7.8 ± 0.2°C, the experiment was divided into two phases: early rearing and a temperature experiment. Early rearing was from hatch to 8 g with diploid and triploid fish held under the same environmental conditions (at 8.4 ± 0.2°C to gradually reach 14.2 ± 0.1°C three weeks after first feeding). The temperature experiment was from 8 to 60 g with diploid and triploid fish exposed to two different temperature regimes: Standard 14°C and High 18°C. Fish were exposed to 24h photoperiod from first feeding onward and fed commercial diets. During early rearing, ploidy had no effect on mortality and growth. Opercular anomalies, predominantly shortness of the operculum, were the most common (88.3 ± 9.7% diploids and 83.3 ± 7.6% triploids) with no significant effect of ploidy. A short lower jaw was the second most common anomaly (10.8 ± 3.4% diploids and 11.7 ± 7.5% triploids), again with no effect of ploidy. LJD prevalence was low (1.7 ± 2.4%) and was first observed at ~7.5 g. ...